The study on factors that influencing level of satisfaction of HRMIS users in Jabatan Audit Negara Negeri Kelantan / Noor Elliana Ahmad Saidi - Ahmad Saidi, Noor Elliana (Bachelor of Science (Hons) Statistics, 2015)
Human Resource Management Information Systems (HRMIS) is on-line system introduces to provide public servants with integrated system for human resources management. It was expected to ease the users of the Information Systems. This is because this systems automating the HRM operational processes which are currently done manually. Unfortunately, the system was complained largely due to unfavorable responses among users towards system. In other words, majority of system users were not satisfied with the applications. This study is hereby to investigate the influential factors that would affect the users’ satisfaction of HRMIS and the relationship between Information Quality, System Quality, and Service Quality with Satisfaction Level of HRMIS Users. The study was carried out to 60 staffs at Jabatan Audit Negara Negeri Kelantan that randomly selected, and then was given questionnaires to collect the data. The data then were analyzed by using Statistical Packages for Social Sciences (SPSS) in forms of frequency, percentage and mean value. After analyzing the data collected, Pearson’s Correlation Coefficient between all three independent variables which are Information Quality, System Quality and Service Quality towards dependant variable which is User Satisfaction. A multiple regression analysis was conducted to estimate the predictor variables that the significant factors that affect satisfaction level of HRMIS Users. The result showed that System Quality could significantly predict Satisfaction Level of HRMIS Users. The result also showed that the best model used in this study is by using Stepwise Procedure. Lastly, appropriate steps had also been stated so that it could be taken thereafter to improve the satisfaction level of HRMIS Users